2015
DOI: 10.1186/s12884-015-0667-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between pelvic girdle pain and sick leave during pregnancy; a retrospective study of a Norwegian population

Abstract: BackgroundThe incidence of pelvic girdle pain (PGP) in pregnancy is wide ranged depending on definition, the utilised diagnostic means, and the design of the studies. PGP during pregnancy has negative effects on activities of daily living and causes long sick leave, which makes it a major public health issue. Our objectives were to explore the frequency of sick leave in pregnancy due to PGP, assess the relationship between different types of pain-related activities of daily living, examine physical workload, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 32 publications
3
48
0
3
Order By: Relevance
“…Some studies show that pain and disability do not increase with advancing pregnancy, whereas other studies have found that they do . In some studies increased pain throughout the course of pregnancy was reported with no influence on disability, while others reports suggest minimal pain and moderate disability related to sacroiliac dysfunction while pregnancy progresses; finally, there is a report of minimal pain but differing degrees of disability, ranging from mild to moderate …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies show that pain and disability do not increase with advancing pregnancy, whereas other studies have found that they do . In some studies increased pain throughout the course of pregnancy was reported with no influence on disability, while others reports suggest minimal pain and moderate disability related to sacroiliac dysfunction while pregnancy progresses; finally, there is a report of minimal pain but differing degrees of disability, ranging from mild to moderate …”
Section: Introductionmentioning
confidence: 98%
“…10 In some studies increased pain throughout the course of pregnancy was reported with no influence on disability, 11 while others reports suggest minimal pain and moderate disability related to sacroiliac dysfunction while pregnancy progresses 12 ; finally, there is a report of minimal pain but differing degrees of disability, ranging from mild to moderate. 13 Owing to these conflicting reports, the present prospective study was performed to determine the incidence of sacroiliac dysfunction during the first trimester of pregnancy and to assess the relationship between pain and disability caused by sacroiliac dysfunction from the beginning to the end of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…PGP can also affect the ability to function in the work place. As a result there is an increased level of sickness absence in working women with PGP (Malmqvist et al, 2015;Mogren, 2006). Gutke et al (2006) found that pregnant women with PGP took significantly more sick leave than pregnant women with only LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Боль в нижней части спины встречается у 45-75% здоровых беременных, частота и интенсивность боли увеличиваются со сроком гестации [14]. Отдельно выделяют боль в области тазового пояса, локализующуюся между задним гребнем подвздошной кости и ягодичной складкой, включая область крестцово-подвздошных суставов, и/или в симфизе [15]. В англоязычной литературе для описания этой боли используется термин «pelvic girdle pain» («боль в области тазового пояса», БТП).…”
Section: те р а п и я н п в п в т е ч е н и е б е р е м е н н о с т иunclassified
“…Причины БТП до конца неясны, среди них обсуждаются гормональные (повышение уровня релаксина, приводящее к расслаблению связочного аппарата таза), биомеханические (изменение осанки, смещение центра тяжести), метаболические (гипокальциемия, гиперглюкоземия), генетические (женщины, матери или сестры которых испытывали БТП, чаще страдают от подобных симптомов) [18,19]. Кроме того, факторами риска являются травма таза в анамнезе, боль в пояснично-крестцовом отделе позвоночника в предыдущие беременности, нагрузка на рабочем месте [15]. Хотя многие врачи считают БТП проявлением нормально протекающей беременности, она оказывает негативное влияние на качество жизни женщин, имеет психосоциальные (послеродовая депрессия встречается в 3 раза чаще у женщин, которые испытывали БТП во время беременности) и экономические (80% женщин с БТП становятся временно нетрудоспособными в течение 12-15 нед) последствия [15,20].…”
Section: те р а п и я н п в п в т е ч е н и е б е р е м е н н о с т иunclassified